The Impact of Structural Reforms on Wages and Employment: The Case of Formal versus Informal Workers in Bolivia - Julius Spatz (Kiel Institute for World Economics (IfW), 2003)
This paper seeks to contribute to the ongoing controversy on the distributional effects of structural reforms in developing countries. To this end, we set up a small-scale macroeconomic model of a dual economy to capture the transmission mechanisms through which the deregulation of product and factor markets, the liberalization of the trade and FDI regime, and the privatization of public companies impact on the distribution of employment and wages between the formal and the informal sector. We empirically test the implications of our theoretical model in a detailed case study on the structural reform process in Bolivia since 1985.
Keywords: O17; L16; D58; J50; 330; Structural Reforms; Informal Sector; Wages; Employment; Bolivia; Anpassungsprogramm des IWF; Wirtschaftspolitische Wirkungsanalyse; Verteilungswirkung; Dualökonomie; Lohn; Beschäftigungseffekt; Schätzung; Theorie; Bolivien